Expected net present value, expected net future value, and the Ramsey rule - Christian Gollier (Center for Economic Studies and ifo Institute (CESifo), 2009)
Weitzman (1998) showed that when future interest rates are uncertain, using the expected net present value implies a term structure of discount rates that is decreasing to the smallest possible interest rate. On the contrary, using the expected net future value criterion implies an increasing term structure of discount rates up to the largest possible interest rate. We reconcile the two approaches by introducing risk aversion and risk-neutral probabilities. We show that if the aggregate consumption path is optimized, the two criteria are equivalent. Moreover, they are also equivalent to the Ramsey rule extended to uncertainty.
Keywords: D61; 330; discount rate; asset price; Ramsey rule; cost-benefit analysis; Kosten-Nutzen-Analyse; Dynamische Investitionsrechnung; Abzinsung; Zinsstruktur; Optimale Besteuerung; Theorie